Method of Estimating Costs of a Software Web Product - Diaz Villegas, Jorge E. (2015)
The costing of a product is a key factor in the marketing process. Its proper calculation can attract customers, which will ensure a company’s life and its business expansion. These considerations have driven the Centre for the Study of software Engineering at Universidad de la Frontera (CEIS-UFRO) to develop a method to define the cost of a web software product, based on use cases and productivity. This method is adaptable to the particular characteristics of any development process, any development team, any product and any company.This article describes the method and performs an initial validation by describing a quasi-experiment designed for Web applications developed by groups of three to five people. We have proved that: a. the method may be reproduced,b. effort estimation is sensitive to the definition of productivity, c. the subjectivity introduced by the estimators does not invalidate the method. For a complete validation of this method, different web products and a larger number of estimatorswith different levels of experience should be incorporated in a future replication.